2024
DOI: 10.1007/s00125-024-06132-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk of diabetic retinopathy and diabetic macular oedema with sodium–glucose cotransporter 2 inhibitors and glucagon-like peptide 1 receptor agonists in type 2 diabetes: a real-world data study from a global federated database

Aikaterini Eleftheriadou,
David Riley,
Sizheng S. Zhao
et al.

Abstract: Aims/hypothesis A protective role of sodium–glucose cotransporter 2 inhibitors (SGLT2is) and glucagon-like peptide 1 receptor agonists (GLP1-ra) in the development of diabetic retinopathy and diabetic macular oedema has been described in some recent studies, which may extend beyond glycaemic control. We aimed to review the clinical impact of SGLT2i and GLP1-ra therapy on the risk of diabetic retinopathy and diabetic macular oedema in individuals with type 2 diabetes taking insulin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Individuals with serious gastrointestinal conditions such as Gastroparesis and inflammatory bowel disease should also avoid GLP-1 analogs. Very recently, it has been reported that monotherapy with GLP-1 is associated with a risk of new-onset nonproliferative diabetic retinopathy, Diabetic retinopathy, and diabetic macular edema [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with serious gastrointestinal conditions such as Gastroparesis and inflammatory bowel disease should also avoid GLP-1 analogs. Very recently, it has been reported that monotherapy with GLP-1 is associated with a risk of new-onset nonproliferative diabetic retinopathy, Diabetic retinopathy, and diabetic macular edema [56,57].…”
Section: Discussionmentioning
confidence: 99%